Advancing Shale Gas Recovery with Microwave Heating: A Study of Frequency, Time, and Thermal Effects in Reservoir Stimulation - Dike F Putra; Novi Lestari Yuliani; Neneng Purnamawati; Novrianti Novrianti; Mohd Zaidi Jaafar (Testing Center for Oil and Gas LEMIGAS, 2025)
The advancement of unconventional hydrocarbon reservoirs, especially shale gas, has revolutionized energy production, offering a cleaner alternative to traditional fossil fuels. Despite its potential, shale gas extraction faces significant challenges due to the ultra-low permeability of formations, complex pore structures, and issues like water blocking caused by hydraulic fracturing fluids. This study explores the innovative application of microwave heating (MWH) as a Formation Heat Treatment (FHT) technique to mitigate these challenges and enhance shale gas recovery. Microwave heating operates by converting electromagnetic energy into heat, leveraging the dielectric properties of reservoir materials to generate rapid, uniform, and volumetric heating. Numerical simulations were conducted to evaluate the effectiveness of MWH under varying frequencies (915 MHz, 2450 MHz, and 5800 MHz), focusing on temperature distribution, water volume reduction, and gas production. Results demonstrate that higher microwave frequencies, particularly 5800 MHz, lead to significant temperature increases, effective water vaporization, and permeability improvements. This process facilitates gas desorption from the shale matrix, enhances diffusion, and improves cumulative gas recovery. The study highlights the environmental advantages of MWH, including reduced water usage and avoidance of groundwater contamination, positioning it as a sustainable alternative to traditional hydraulic fracturing. Furthermore, insights into shale reservoirs' thermal and electromagnetic properties are provided, offering guidance for optimizing MWH application in field conditions. This research underscores the potential of MWH to address critical operational challenges in unconventional reservoirs, paving the way for its integration into advanced shale gas recovery strategies.